CERTAIN ASPECTS OF COMPULSION OF MARRIAGE IN CONDITIONS OF MARTIAL STATUS - Kulikov, Oleksii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is an analysis of forced martial law and the development of theoretical and practical recommendations to combat this phenomenon. Methods: general and special scientific (special) were used to achieve a certain goal. The use of these methods allowed to outline the problems of coercion in marriage in terms of criminal law and criminology. Results: in the pre-war period, the statistics of forced marriage were low, due to a number of factors: low awareness of the population and law enforcement officers about the existence of this legal structure; natural high latency of such offenses that have a certain relation to the sexual sphere; lack of clear methodological recommendations on the specifics of the investigation of this category of criminal offenses; the presence of archaic social attitudes about the role of women in the family. Insufficient attention of clergy and civil registry officials to whether the desire to marry is a valid expression of the will of the parties, or arose as a result of coercion. In the context of armed aggression, several additional questions arise. The first is forced marriages with local women, which are committed by enemy soldiers, in conditions of armed aggression. Taking advantage of the de facto impossibility of establishing the actual marital status of brides, disconnection from state registers and threats with the use of weapons by the occupier, many servicemen «married» in the occupied territories for the second, third or even fourth time. It is also worth noting that during martial law there are certain features of marriage registration. First of all, the marriage registration procedure has been accelerated, it is registered mostly on the day of application. At the same time, even the procedure for expedited marriage registration is not available to many in hostilities. In such cases, the Family Code of Ukraine allows for the recognition of a marriage registered in accordance with a religious ceremony. However, the observance of the principles of voluntariness and monogamy essentially remains the responsibility of the bride and groom, because the priest can not verify the accuracy of such data.